Protein ISGylation: a posttranslational modification with implications for malignant neoplasms - Angeles C. Tecalco-Cruz; Jesús Zepeda-Cervantes (Open Exploration Publishing Inc., 2023)
Interferon (IFN)-stimulated gene 15 (ISG15) is a member of the ubiquitin-like (UBL) protein family that can modify specific proteins via a catalytic process called ISGylation. This posttranslational modification can modulate the stability of the ISGylated proteins and protein-protein interactions. Some proteins modified by ISG15 have been identified in malignant neoplasms, suggesting the functional relevance of ISGylation in cancer. This review discusses the ISGylated proteins reported in malignant neoplasms that suggest the potential of ISG15 as a biomarker and therapeutic target in cancer.